PELAKSANAAN PENJATUHAN SANKSI ADMINISTRASI TERHADAP PEGAWAI NEGERI SIPIL YANG MELAKUKAN TINDAK PIDANA PENIPUAN: Implementation Of Imposing Administrative Sanctions Against Civil Servants Who Commit Fraud Crimes - Muhammad Syukur Fezadi Iskandar; Yogo Pamungkas (Faculty of Law, Universitas Trisakti, 2024)
State Civil Apparatus assist in carrying out the government's duties to achieve Indonesia's national goals. However, issues arise when a Civil Servant is dismissed for actions detrimental to the state. This research addresses two main questions: whether the administrative sanctions were imposed in accordance with statutory regulations, and whether they complied with Law Number 5 of 2014 concerning State Civil Apparatus. The research method is qualitative, employing normative legal research. The findings reveal that the dismissal decree was not based on appropriate legislation, as the Plaintiff had pursued a legal remedy through cassation. However, the sanctions were in accordance with Law Number 5 of 2014, as the Plaintiff was found guilty of fraud and sentenced to 2 years and 8 months in prison. The conclusion is that the Defendant erred in their consideration of the administrative sanction, basing it on the Bengkulu District and High Courts' decisions, which had not yet gained permanent legal force. Thus, the dismissal is deemed invalid